Flow Analysis of a 300 MW F-Class Heavy-Duty Gas Turbine 1.5 Stage Compressor - Kunhang Li; Bo Song; Suyu Jiang; Jiao Wang; Xiaojun Fan; Jingyin Li (Aerospace)
The axial compressor is crucial for heavy-duty gas turbines, with its aerodynamic performance directly affecting efficiency. The current trend in the development of these compressors is to increase the stage load and efficiency, thereby achieving a higher pressure ratio with fewer stages. The aerodynamic characteristics of a 1.5-stage axial compressor from a 300 MW F-class heavy gas turbine at three different rotation speeds (100%, 90%, and 80%) were studied. Specifically, the distribution of the inlet Mach number, shock wave structures, isentropic Mach number of blade surface, and blade surface separation flow characteristics under three typical working conditions, at the near stall (NS) point, maximum efficiency (ME) point, and near choke point (NC), were discussed. The results indicate that at 80% rotational speed, 70~100% spanwise of the compressor rotor blade is operated under the transonic zone. Meanwhile, at 100% rotational speed, almost all the spanwise of the compressor rotor blade is operated under the transonic zone. Furthermore, compared to the detached shock wave observed under the NS condition, the normal passage shock wave observed under the NC condition exhibits more significant changes in shock intensity and shock pattern.